Designing for Comm[unity] Em[power]ment: A sustainable multi-purpose sports facility for social and environmental Impact - Buthelezi, Mvelo Hilton Nkosinathi (University of the Witwatersrand, Johannesburg, 2024)
This master’s thesis focuses on the critical need for sports infrastructure in Africa, particularly in underdeveloped regions such as Alexandra Township. Sports are hindered by inadequate infrastructure and neglect, limiting potential for social and economic progress on the continent. This thesis attempts to create a multi-purpose sports complex in Alexandra Township that encourages community engagement, social empowerment, and environmental sustainability while also meeting immediate infrastructure demands. The primary goal of this thesis is to construct a sports facility that can accommodate people of all ages and ability levels, fostering an active lifestyle and improving physical and mental well-being. The planned sports complex integrates adaptable architecture, including flexible and modular features to meet changing demands.These adaptable modules are intended for application in a variety of communities across the country, maintaining the facility’s long-term usefulness. Beyond typical sporting activities, the stadium will incorporate mixed-use facilities with amenities such as educational rooms, leisure spaces, cafés, retail sections, and green spaces. An agriculture facility will also aid to cheap distribution of fresh goods throughout the neighborhood. Waste management solutions will help to make the environment cleaner and healthier. To summarize, the goal of this architectural master’s thesis is to design an adaptable, community-centered sports facility near Alexandra Township that not only provides accessible and high-quality sports infrastructure but also promotes social cohesion, environmental stewardship, and personal development. The facility aims to catalyze positive change by blending adaptable architectural concepts and mixed-use areas, influencing other communities to promote sports, community participation, and environmental responsibility. We hope to create a pattern for future architectural endeavors in the region by contributing to the overall well-being and empowerment of residents in Alexandra Township through this thesis.
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Sustainability; modular construction; moveable structure; ports architecture; SDG-8: Decent work and economic growth; SDG-8: Decent work and economic growth